2017
DOI: 10.1007/s10792-017-0593-4
|View full text |Cite
|
Sign up to set email alerts
|

Complete corneal ring (MyoRing) implantation versus MyoRing implantation combined with corneal collagen crosslinking for keratoconus: 3-year follow-up

Abstract: PurposeTo estimate the effectiveness of complete corneal ring (MyoRing) implantation compared with MyoRing implantation combined with corneal collagen crosslinking (CXL) for keratoconus treatment for 36 months follow-up.DesignRetrospective cohort study.Materials and methodsMyoRing implantation was performed in a series of 78 patients (80 eyes) with keratoconus II–III Amsler classification, of these 39 eyes had MyoRing implantation combined with CXL. Implantation of a MyoRing in the corneal pocket was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…The present study showed that, after KeraRing and MyoRing implantation, CCT does not generally change; however, the CCT decreased at central 4 mm after MyoRing implantation, and this change was statistically significant. This effect might be due to the special design of the ring and its depth of implantation, as also mentioned in another study [ 19 ]. The study by Zare indicated that, after Intacs implantation, the cornea thickness increased within the first month after surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 78%
“…The present study showed that, after KeraRing and MyoRing implantation, CCT does not generally change; however, the CCT decreased at central 4 mm after MyoRing implantation, and this change was statistically significant. This effect might be due to the special design of the ring and its depth of implantation, as also mentioned in another study [ 19 ]. The study by Zare indicated that, after Intacs implantation, the cornea thickness increased within the first month after surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 78%
“…Using microkeratome pocket maker, Myoring significantly enhanced UCVA and CDVA from 1.06 to 0.49 logarithm of minimum angle of resolution (LogMAR) to 0.3 and 0.28 after 36 months respectively. SE, as well, was significantly decreased from −7.8 to −1.6 D and the average k readings similarly were reduced from 50.2 to 40.8 D [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“… 19 21 Nevertheless, other authors outlined the need for additional evidence to confirm this claim. 22 …”
Section: Introductionmentioning
confidence: 99%